Establishing the range of variability of the skull structures in adulthood - Sazonova, Olga; Vovk, Oleg; Hordiichuk, Daria; Ikramov, Volodimir; Onashko, Yulia (Journal of Education, Health and Sport, 2017)
One of the most relevant direction of modern craniological anatomy ̶ is an individual variability of the shape, size, position and relations of skull’s regions and their structures. The research was conducted on craniometric study of 100 coherent and fragmented skull’s bones included in the collections of human anatomy department in Kharkiv National Medical University. For facial skull studies used different measuring instruments and devices: dividers, set of facial lines, protractors, goniometer.In adulthood people of our region there is a direct dependence on the morphological type of the structures of the head and certain indicators of the cranial, altitude-longitudinal and altitude-latitudinal indexes. Most often, there are males with expanded and rounded forms of the skull with a predominance of moderate head size, that is relate them to the brachicranial type of the skull’s structure. The middle group consists of males and females who have a classical middle form of the head, and belong to the mesomorphic structure of the skull. The smallest group consists of adulthood people with a narrow and elongated form of the head, referred to the dolichocranial type of skull structure.